Patients with recurrent biliary tract cancer have a better prognosis than those with unresectable disease: retrospective analysis of a multi‐institutional experience with patients of advanced biliary tract cancer who received palliative chemotherapy. Issue 2 (20th June 2013) - Ikezawa, Kenji; Kanai, Masashi; Ajiki, Tetsuo; Tsukamoto, Tadashi; Toyokawa, Hideyoshi; Terajima, Hiroaki; Furuyama, Hiroaki; Nagano, Hiroaki; Ikai, Iwao; Kuroda, Nobukazu; Awane, Masaaki; Ochiai, Toshiya; et al.
Abstract Background Prognostic factors for patients with advanced biliary tract cancer (BTC) who received palliative chemotherapy have not been fully established. Especially, the status of unresectable/recurrent disease has not been well studied because of a small number of patients with recurrent BTC in previous studies. Methods This multicenter retrospective study was conducted in 18 institutions in Japan. We retrospectively reviewed data regarding 403 patients with pathologically proven BTC who received palliative chemotherapy between April 2006 and March 2009. One hundred and ninety‐two patients with recurrent BTC were included. Univariate and multivariate analyses were performed to identify prognostic factors. Results The median overall survival was significantly longer in the recurrent BTC patients than in the unresectable BTC patients (398 days vs. 323 days, P = 0.004). After adjustment using multivariate analysis, the status of recurrent/unresectable disease remained an independent prognostic factor (hazard ratio 1.33, 95% confidence interval 1.04–1.70, P = 0.022) in addition to performance status, extent of disease, carbohydrate antigen 19‐9 levels, and carcinoembryonic antigen levels. Conclusions The status of unresectable/recurrent disease was shown as an independent prognostic factor in the BTC patients. This result may help to predict life expectancy of BTC patients and design future clinical trials evaluating palliative chemotherapy in BTC.